Bionanotechnology for vaccine design. (August 2018) - Frey, Steven; Castro, Ana; Arsiwala, Ammar; Kane, Ravi S
Graphical abstract: Highlights: Many vaccines display antigens multivalently to enhance the immune response. Diverse nanostructured scaffolds have been developed for multivalent antigen display. Advances in bionanotechnology will lead to the design of more effective vaccines. Abstract : There have been significant advances in the design of nanostructured scaffolds for eliciting robust immune responses. One method to produce strong immune responses is to emulate the appearance of a pathogen. Since pathogens such as viruses and bacteria often display multiple copies of ligands on their surfaces, the immune system is particularly sensitive towards multivalent displays of antigens. Consequently, when designing a vaccine, it is advantageous to decorate a nanostructured surface with multiple copies of an antigen. This review highlights the design and efficacy of a diverse set of recently developed nanostructured vaccine scaffolds.